If f(x) = x² + 3, then f(x + y) = ?
A.) x² + 2xy + y² + 3 B.) x² + 2xy + y² C.) x² + 2xy + 3 D.) x² + 3 + y E.) x² + y²
If f(x) = x² + 3,
then f(x+ y) = (x + y)² + 3 {substituted (x + y), in for x, into f(x) = x² + 3} = (x + y)(x + y) + 3 {when squaring a binomial, multiply it by itself} = x² + 2xy + y² + 3 {used FOIL method / distributive property to multiply} A.) x² + 2xy + y² + 3 Ask Algebra House Comments are closed.

ACT Practice Playlist
ACT is a registered trademark of ACT, Inc. SAT is a registered trademark of the College Board. ACT and SAT are not affiliated with this site.
Archives
March 2021
